Arrangement and Decomposition of Grain Boundary Dislocations: Two-Mode Phase-Field Crystal Simulation - Li, Huanqing; Wang, Xiaona; Zhang, Haibin; Tian, Xiaolin; Hou, Hua; Zhao, Yuhong (Frontiers in Materials, 2022)
The grain boundary dislocations arrangement and decomposition during constant volume deformation of nanoscale bi-crystal system in fcc-structured materials studied by using the two-mode phase field crystal (2PFC) method. The effects of different grain boundary misorientations (GBMs) and tensile deformation directions on the dislocations arrangement and decomposition are analyzed. Three different symmetrical tilt grain boundaries evaluated by PFC, the atomic density profile of grain boundaries changed periodically at equilibrium. The initial grain boundary dislocation arrangement of the three samples is almost the same when tensile deformation is applied to the samples in the x- or y- direction and all are symmetrically arranged in a "bowknot " structure. The stress at the grain boundary is concentrated with the increase of strain, and dislocation decomposition can effectively reduce the stress concentration. The time steps of dislocations decomposition at grain boundaries decreases with increasing strain rate. The present work facilitates application of PFC in the analysis of grain boundary mechanics in an extended range of materials.